Clinical Outcomes of Osteochondral Fragment Fixation Versus Microfracture Even for Small Osteochondral Lesions of the Talus. Issue 11 (September 2022) - Nakasa, Tomoyuki; Ikuta, Yasunari; Sumii, Junichi; Nekomoto, Akinori; Kawabata, Shingo; Adachi, Nobuo
Background: The bone marrow stimulation (BMS) technique is performed for osteochondral lesions of the talus (OLTs) with a lesion size of <100 mm 2 . The lesion defect is covered with fibrocartilage, and the clinical outcomes deteriorate over time. In contrast, the osteochondral fragment fixation can restore the native articular surface. The difference in clinical outcomes between these procedures is unclear. Purpose: To compare the clinical outcomes of BMS and osteochondral fragment fixation for OLTs and examine the characteristics of patients with poor clinical outcomes of BMS. Study Design: Cohort study; Level of evidence, 3. Methods: In total, 62 ankles in 59 patients with OLTs were included. BMS was performed for 26 ankles, and fixation was performed for 36 ankles. Clinical outcomes, including the American Orthopaedic Foot & Ankle Society (AOFAS) Ankle Hindfoot Scale and bone marrow edema (BME) as identified on magnetic resonance imaging, were compared between the 2 groups. On computed tomography scans, the lesion location was compared with or without BME in each group. Results: The AOFAS scores in the fixation group (97.3 ± 4.3 points) were significantly higher than those in the BMS group (91.3 ± 7.7 points), even when the lesion size was <100 mm 2 ( P < .05). When comparing the ankles with or without BME in each group, the AOFAS scores at the final follow-up were significantly lower for the ankles with BME (88.6 ± 7.8 points) than for those without BME (95.0 ± 6.1 points) in the BMS group ( P < .05). Lesions with BME in the sagittal plane were located more centrally than those without BME in the BMS group. In the fixation group, there were no significant differences in AOFAS scores and location of the lesion in ankles with or without BME. Conclusion: The clinical outcomes of osteochondral fragment fixation are superior to those of BMS in OLTs, even for lesions sized <100 mm 2 . Fixation is recommended even for small lesions, especially for more centralized lesions in the medial and lateral sides of the talus.